Research and Application Progress of Laser Cladding Metal Protective Coatings in the Thermal Power Field - HU Han, XU Jinyong, WU Duoli, WEI Xinlong, LI Yong, ZHANG Chao (Cailiao Baohu)
Laser cladding technology has become an important means of improving the surface performance of components in modern manufacturing， particularly demonstrating its unique advantages in the repair and remanufacturing of power plant equipment.This paper reviewed different types of laser cladding processes and their research and applications in improving material wear resistance， corrosion resistance and other properties.The latest advancements in the application of laser cladding technology in the thermal power plant field were discussed， along with its progress in supercritical and ultra-supercritical power plants.The excellent performance of materials such as Hastelloy alloys and nickelbased alloys during the laser cladding process was detailed，including the ceramic particle reinforcement，the selection of elemental composition and the optimization of process parameters.Furthermore，the challenges faced by laser cladding technology and its future development directions were explored， including the optimization of process parameters， the preparation of new coating materials， and the development of new technologies to improve cladding efficiency and coating quality.Laser cladding technology can effectively improve the durability and reliability of power generation equipment， especially in high-temperature and high-pressure environments under supercritical/ultra-supercritical conditions.The future development challenges of laser cladding technology are primarily focused on the further optimization of process parameters， the development of new coating materials， and the development of new technologies to improve cladding efficiency and coating quality.Addressing these challenges will significantly enhance the durability and reliability of power generation equipment in high-temperature and high-pressure environments， providing crucial support for the sustainable development of this field.